Le développement des utilisations non alimentaires de l’huile de colza dans l’UE : quels impacts sur les marchés et prix mondiaux ?1 - Dronne Yves; Gohin Alexandre (Oléagineux, Corps gras, Lipides, 2005)
For some years, biodiesel production, based mainly on rapeseed oil, has registered a big progression, and important investments are on stream for the next years. The analysis of recent evolution of European and international rapeseed products suggests that this development has already significant effects in term of increase in cultivated area and crops, diminution of EU exportation positive balance for this seed and oil, and evolution of prices ratios for oils and meals. This hypothesis is confirmed by results obtained with OLEOSIM model simulating the effect of an exogenous shock of demand of this oil inside EU. Nevertheless the influence of other factors remains very strong, some of these factors are depending on the economic and climatic situation, some others are structural such as the withdrawal of EU from Canadian rapeseed export market. In a middle term situation, the prices spreads between rapeseed and other vegetable oils, due to the only biodiesel development should be weaker than during 2005 year.